Analysis of The Operational Risk Management of Ethno Bali Foundation Bee Agrotourism in Baha, Mengwi Village - PURVITASARI, EVIE - (Journal of Agribusiness, Social and Economic, 2023)
Tourism is one of the largest and fastest-growing economic sectors in the world. One of the areas that has the best potential in terms of agro-tourism is the Bali area. Bali is the area that is most in demand, so it is not surprising that many foreign tourists and local tourists make Bali their favorite tourist destination.The method used in this research is quantitative descriptive research. The total number of respondents in this study was 25. Operational risk of a company to be able to know the right action decisions in minimizing risk needs to process the calculation of the level of impact and the level of possibility through the Godfrey method. These 10 risks are the most intense risks occurring in the Etno Bali Foundation Bee Agrotourism. The risks in the Lebah Etno Bali Foundation Agrotourism occur due to a less than optimal system, both from HR (Human Resources) to the management of the facilities there1.The results showed that the operational risks identified in the Etno Bali Foundation Bee Agrotourism Unit were 11 types of risks and. Efforts to address operational risk are prioritized have high and extreme levels through preventive and mitigating efforts.